Molecular insights into glioblastoma progression: role of CHCHD2P9 in tumor heterogeneity and prognosis - Ding, Yanyu; Xiao, Lizhi; Zhou, Xiaoling; Zhao, Jiaxin; Ke, Jianli; Cai, Huabao; Zhao, Mengyu; Wang, Cunzhi; Yu, Tianhang; Zhao, Zhijie; Wang, Yucai; Ke, Jiyuan (Frontiers in Immunology, 2025)
BackgroundGliomas are highly aggressive, life-threatening tumors with poor prognosis, and remain a leading cause of mortality among brain cancers. Although the role of mitochondrial proteins in cancer has garnered increasing attention, their specific functions in the nervous system, particularly in gliomas, remain poorly understood.MethodsWe integrated single-cell RNA sequencing with cellular assays and flow cytometry to investigate the molecular characteristics and cellular interactions within glioblastoma subpopulations during tumor progression.ResultsSingle-cell RNA sequencing revealed several differentially expressed genes (DEGs) within glioblastoma subpopulations. Trajectory analysis identified CHCHD2P9 as a pivotal marker for the terminal subpopulation. Moreover, elevated expression of CHCHD2P9 was found to correlate with poorer clinical outcomes. Subsequent cellular experiments further explored the underlying mechanisms driving these observations.ConclusionsCHCHD2P9 is significantly overexpressed in glioma patients, and its differential expression plays a crucial role in regulating glioma cell proliferation and migration. A CHCHD2P9-based risk model holds promise as both a prognostic biomarker and a potential therapeutic target, providing novel insights into the pathogenesis of gliomas and opening avenues for personalized treatment strategies.